Increased cell stiffness contributes to complement‐mediated injury of choroidal endothelial cells in a monkey model of early age‐related macular degeneration. Issue 3 (8th April 2022) - Cabrera, Andrea P; Stoddard, Jonathan; Santiago Tierno, Irene; Matisioudis, Nikolaos; Agarwal, Mahesh; Renner, Lauren; Palegar, Neha; Neuringer, Martha; McGill, Trevor; Ghosh, Kaustabh
Abstract: Age‐related macular degeneration (AMD) is the leading cause of blindness in the aging population. Yet no therapies exist for 85% of all AMD patients who have the dry form that is marked by degeneration of the retinal pigmented epithelium (RPE) and underlying choroidal vasculature. As the choroidal vessels are crucial for RPE development and maintenance, understanding how they degenerate may lead to effective therapies for dry AMD. One likely causative factor for choroidal vascular loss is the cytolytic membrane attack complex (MAC) of the complement pathway that is abundant on choroidal vessels of humans with early dry AMD. To examine this possibility, we studied the effect of complement activation on choroidal endothelial cells (ECs) isolated from a rhesus monkey model of early AMD that, we report, exhibits MAC deposition and choriocapillaris endothelial loss similar to that seen in human early AMD. Treatment of choroidal ECs from AMD eyes with complement‐competent normal human serum caused extensive actin cytoskeletal injury that was significantly less pronounced in choroidal ECs from young normal monkey eyes. We further show that ECs from AMD eyes are significantly stiffer than their younger counterparts and exhibit peripheral actin organization that is distinct from the longitudinal stress fibers in young ECs. Finally, these differences in complement susceptibility and mechanostructural properties were found to be regulated by the differential activity of the small GTPases Rac and Rho, because Rac inhibition in AMD cells led to simultaneous reduction in stiffness and complement susceptibility, while Rho inhibition in young cells exacerbated complement injury. Thus, by identifying cell stiffness and cytoskeletal regulators Rac and Rho as important determinants of complement susceptibility, the current findings offer a new mechanistic insight into choroidal vascular loss in early AMD that warrants further investigation for assessment of translational potential. © 2022 The Pathological Society of Great Britain and Ireland.